Developmental signature, synaptic connectivity and neurotransmission are conserved between vertebrate hair cells and tunicate coronal cells. Issue 6 (25th January 2018) - Rigon, Francesca; Gasparini, Fabio; Shimeld, Sebastian M; Candiani, Simona; Manni, Lucia
Abstract: In tunicates, the coronal organ represents a sentinel checking particle entrance into the pharynx. The organ differentiates from an anterior embryonic area considered a proto‐placode. For their embryonic origin, morphological features and function, coronal sensory cells have been hypothesized to be homologues to vertebrate hair cells. However, vertebrate hair cells derive from a posterior placode. This contradicts one of the principle historical criteria for homology, similarity of position, which could be taken as evidence against coronal cells/hair cells homology. In the tunicates Ciona intestinalis and C. robusta, we found that the coronal organ expresses genes ( Atoh, Notch, Delta‐like, Hairy‐b, and Musashi ) characterizing vertebrate neural and hair cell development. Moreover, coronal cells exhibit a complex synaptic connectivity pattern, and express neurotransmitters (Glu, ACh, GABA, 5‐HT, and catecholamines), or enzymes for their synthetic machinery, involved in hair cell activity. Lastly, coronal cells express the Trpa gene, which encodes an ion channel expressed in hair cells. These data lead us to hypothesize a model in which competence to make secondary mechanoreceptors was initially broadly distributed through placode territories, but has become confined to different placodes during the evolution of the vertebrate and tunicate lineages. Abstract : Coronal sensory cells of tunicates have been hypothesized to be homologues to vertebrate hair cells. Coronal cells differentiate from an anterior proto‐placode, whereas vertebrate hair cells derive from a posterior placode. In Ciona, coronal cells express genes characterizing vertebrate hair cell in development and neurotransmission/transduction activity, and a similar complex synaptic connectivity pattern. These data lead us to hypothesize a model in which competence to make secondary mechanoreceptors was initially broadly distributed through placode territories, but became confined during evolution.